Interprofessional dietary assessment practices in primary care: A mixed-methods study. Issue 1 (2nd January 2016) - Bonilla, Carolina; Brauer, Paula; Royall, Dawna; Keller, Heather; Hanning, Rhona M.; DiCenso, Alba
ABSTRACT: Patients in primary care (PC) are often counselled on diet, and assessment of current food intake is a necessary prerequisite for individualized nutrition care. This sequential mixed-methods study explored current diet assessment (DA) practices in team-based PC in Ontario, Canada, with interdisciplinary focus groups (FGs) followed by a web-based survey. Eleven FGs ( n = 50) discussed key patient groups and health conditions requiring DA, as well as facilitators and barriers to accurate DA. Interpretative analysis revealed three themes: DA as a common activity that differed by health profession, communication of DA results within the team, and nutrition care as a collaborative team activity. A total of 191 providers from 73 Family Health Teams completed the web-based survey, and confirmed that many providers are frequently doing DA and that methods vary by discipline. Most providers conducted DAs every day or almost every day. As expected, dietitians used more formal and detailed methods to assess diet than other disciplines, who were more likely to ask a few pointed questions. These baseline data provide information on the range of current DA practices in team-based PC that can inform development of new, more accurate approaches that may improve counselling effectiveness.